Interleukin‐15 inhibits the expression of differentiation markers induced by Ca2+ in keratinocytes. Issue 7 (12th May 2016) - Luo, Xin; Jin, Rui; Wang, Fang; Jia, Bo; Luan, Kang; Cheng, Feng‐Wei; Li, Lei; Sun, Liang‐Dan; Yang, Sen; Zhang, Sheng‐Quan; Zhang, Xue‐Jun
Abstract: Interleukin (IL)‐15 is an important proinflammatory cytokine that can protect epidermal keratinocytes (KCs) from ultraviolet‐induced apoptosis and plays a role in the pathogenesis of psoriasis. However, the impact of IL‐15 on KC differentiation remains unknown. In this study, isolated human primary epidermal KCs were treated with various concentrations of IL‐15 for different times, and the expression of differentiation markers (keratin 1, involucrin and loricrin) and p53 as well as the activation of ERK, AKT and Notch induced by IL‐15 in the absence or presence of Ca 2+ was detected by real‐time PCR and Western blot. The results showed that stimulation with Ca 2+ alone increased the expression of KC differentiation markers and p53 and promoted the activation of Notch1. Pretreatment with IL‐15 resulted in a decrease in the Ca 2+ ‐induced expression of KC differentiation markers and p53. Additionally, Ca 2+ continually inhibited the phosphorylation of ERK1/2 and activated AKT, and IL‐15 reduced the effect of Ca 2+ on ERK1/2 and AKT. FR180204, a specific inhibitor of ERK1/2 phosphorylation, slightly attenuated the effect of Ca 2+ on the expression of differentiation markers and p53 and the activation of Notch1. In contrast, MK‐2206, an inhibitor of pAKT, strongly blocked the expression of the differentiation markers and p53 and the activation of Notch1. An anti‐IL‐15 antibody neutralized the effect of IL‐15 on KC differentiation. These results indicate that IL‐15 inhibits the Ca 2+ ‐induced differentiation of KCs, mainly via the attenuation of Ca 2+ ‐stimulated PI3K‐AKT signalling.